Online shopping: an exercise with Malaysian and Thai product and service e-commerce websites / Dr. Kiranjit Kaur … [et al.] - Kaur, Kiranjit (Dr.) Associate Professor; Iyer, Mangalam Gopala (Associate Professor); Abdul Jabar, Noraziah; Abdul Hamid, Norliza (2005)
This study is to determine the quality of service provided by Malaysian and Thai web vendors. The researchers undertook the shopping experience themselves in order to gain first hand information on the real problems that consumers face when shopping online. Various aspects of quality were examined such as accessibility, reliability, efficiency, ease of use, security and information. The study is based on a qualitative examination of Malaysian and Thai e-commerce websites offering online transactions. Thirty websites were selected for the study - 18 Malaysian sites and 12 Thai sites. The researchers used four sets of protocols to obtain data and information on e-commerce transactions. Three protocols were used for purchasing products online including one each for placing the order, arrival of goods, and returning of goods; and one protocol was used for booking services. Websites of traders offering services seemed to be more efficient than those selling products. This could be because payment was seldom required in booking services as opposed to when placing an order for a product. Most problems were faced in the payment procedure, cancellation of orders, and request for refunds. The study recommends that web traders should provide more easily accessible information on security and privacy issues as well as clear information on cancellation of orders and refunds to promote shopping online and to build confidence in their consumers. It also suggests that the traders upgrade their sites to be more online savvy and update information on them more regularly.